Probing an adhesion mutant of Dictyostelium discoideum with cDNA clones and monoclonal antibodies indicates a specific defect in the contact site A glycoprotein - Noegel, A. (1985)
Expression of developmentally regulated membrane proteins of aggregating cells of Dictyostelium discoideum is subject to several control mechanisms. One of them involves periodic cyclic-AMP pulses as signals for gene expression. To increase the probability of selecting mutants specifically defective in the contact site A (csA) glycoprotein, one of the characteristic proteins of aggregating cells, we have bypassed the requirement for both cyclic-AMP pulses and another control element by two runs of mutagenesis. A `double bypass' mutant, HG592, was obtained which aggregated in nutrient medium where wild-type did not develop. Mutants defective in expression of the csA-glycoprotein were selected from HG592 by fluorescence-activated cell sorting and colony immunoblotting using a monoclonal antibody specific for that protein. One among 51 csA-negative mutants, HG693, specifically lacked the capability of forming EDTA-stable intercellular contacts. It acquired chemotactic responsiveness and developed into fruiting bodies. Expression of the transcripts for eight developmentally regulated proteins was determined in HG693. Seven of the RNA species were normally expressed; they were recognized by cDNA clones which had been produced from poly(A)(+) RNA isolated from membrane-bound polysomes. The single RNA species which was not substantially expressed in HG693 was recognized by a cDNA clone that was obtained by screening a λgt11 library with an antibody specific for the csA-glycoprotein. When probing RNA from wild-type cells, this clone hybridized with a single developmentally regulated RNA species of 1.9 kb whose expression was strongly enhanced by cyclic-AMP pulses. Appearance of this RNA coincided with the expression of the csA-glycoprotein.